Unveiling Barriers to Decolonizing ELT at The Pre-University Level: Stakeholder Resistance and Systematic Barriers in Bangladesh - Shorna Akter (International Journal of Education, Language, and Religion, 2026)
AbstractBased on the pedagogical feasibility of Communicative Language Teaching (CLT) in English Language Teaching (ELT) in non-native contexts, a growing body of research recognizes the importance of incorporating local epistemologies to reduce social and psychological distance within the pedagogical environment, facilitating the development of English skills. Moreover, over-reliance on imported ELT materials has proven ineffective, and therefore, the need for the decolonization of this conventional approach has become obvious (Akter, 2025). Considering the pedagogical scope of incorporating Bengali literature into the ELT classroom to support learners' English language development, the present endeavor aims to investigate the sequential phenomena that may arise from implementing a decolonizing approach to designing learning tools and activities using Bangla literature, and to identify any subsequent tensions that may emerge among stakeholders. Grounded in the post-method approach (Kumaravadivelu, 2001) and the perspective of translanguaging (García, 2009), the present qualitative study collected data through Focus Group Discussion (FGD) with the authoritative bodies of the three colleges, the teachers, and the guardians. The significant findings include deep-seated socio-cultural anxieties among stakeholders, institutions' tendency to avoid risk for good results, and, above all, teachers' reluctance to adopt any change for the pedagogical context due to their unpreparedness and lack of context-dependent assessment models.